The Ecology and Economics of Florida's Ranches - Martin B. Main; Mickey E. Swisher; Jeff Mullahey; William DeBusk; Avrum J. Shriar; George W. Tanner; James Selph; Patrick Hogue; Patrick Bohlen; Ginger M. Allen (EDIS)
Ranching is important to Florida's economy and environment. Of Florida's 34.5-plus million acres of land, 10.2 million acres were utilized for farmland in 2003, with the majority partially or totally used for cattle production. Cattle production contributed more than $348 million to the state's economy in 2003. Ranching helps protect water resources, provides natural greenways for wildlife and recreation, and preserves many components of the natural landscape. Both the environmental and economical health of ranching are therefore critical to the state's citizens. This document is WEC 187, one of a series of the Wildlife Ecology and Conservation Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published as Extension document SS-SA-8, February 2000; revised September 2004.